2020
DOI: 10.3389/fcimb.2020.00400
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer-Associated Fusobacterium nucleatum May Originate From the Oral Cavity and Reach Colon Tumors via the Circulatory System

Abstract: Fusobacterium nucleatum is a common oral bacterium that is enriched in colorectal adenomas and adenocarcinomas (CRC). In humans, high fusobacterial CRC abundance is associated with chemoresistance and poor prognosis. In animal models, fusobacteria accelerate CRC progression. Targeting F. nucleatum may reduce fusobacteria cancer progression and therefore determining the origin of CRC F. nucleatum and the route by which it reaches colon tumors is of biologic and therapeutic importance. Arbitrarily primed PCR per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 48 publications
7
148
2
1
Order By: Relevance
“…Studies show that cancerous tissues contain significantly more Fusobacteria [ 73 ]. Previous research has indicated that infection with this bacterium increases the incidence of ulcerative colitis in which inflammation of the intestinal lining destroys the intestinal cells and consequently is a risk factor for colorectal cancer [ 27 ].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Studies show that cancerous tissues contain significantly more Fusobacteria [ 73 ]. Previous research has indicated that infection with this bacterium increases the incidence of ulcerative colitis in which inflammation of the intestinal lining destroys the intestinal cells and consequently is a risk factor for colorectal cancer [ 27 ].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The notion that CRC-associated F. nucleatum originates from the oral cavity is supported by findings that identical strains of this organism are detected in the saliva and colorectal tumours of patients with CRC 115 . Oral F. nucleatum can haematogenously reach the colon 116 , where it exhibits tropism for CRC. This is because CRC cells overexpress a carbohydrate moiety (Gal-GalNAc) that is bound by the F. nucleatum lectin Fap2 (ref.…”
Section: Direct Effects Of Periodontal Bacteriamentioning
confidence: 99%
“…However, it is not yet clear how Fn reaches the colon from the oral cavity. Recently some authors reported that Fn may migrate to the colon by descending via the digestive tract or using the circulation system during transient bacteriemia [ 60 , 61 ]. The digestive route would be possible in the case of patients taking drugs that reduce gastric acidity, in this way allowing bacteria to migrate to the colon.…”
Section: Discussionmentioning
confidence: 99%